Exploitative Leadership Research: A Comprehensive Overview - Iftikhar Hussain; Sajjad Hussain; Waqas Noor; Engineer Danish Gul Khattak (Journal of Management Practices, Humanities and Social Sciences, 2024)
This study aims to provide a comprehensive yet concise review of the research on exploitative leadership, structured within a chronological framework. It begins by outlining the early historical context of leadership studies, tracing the development of exploitative leadership as a distinct concept within the broader category of destructive or negative leadership. The review highlights the evolution of the term, exploring its relevance across diverse academic disciplines such as sociology, psychology, and political science, each of which contributes unique perspectives to the understanding of this phenomenon. Key queries addressed include how exploitative leadership has diverged from other destructive leadership forms, such as abusive supervision or authoritarian leadership, and what specific characteristics define exploitative leaders. The study also investigates the various outcomes associated with this leadership style, with a particular focus on how it influences behavioural and attitudinal responses in the workplace. This analysis is framed within multiple theoretical frameworks, including social exchange theory and the conservation of resources model, offering a rich, interdisciplinary approach to understanding its impact. In conclusion, the study identifies and discusses emerging trends in exploitative leadership research, suggesting future directions for empirical inves